EDUCATION AS A TOOL FOR SUSTAINABLE HAPPINESS - Neha Sharma, Prof. J . Rajendran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Education has always been a tool for sustainability of happiness but in due course of time, rather should say since the beginning of the human kind or mankind we have been not able to define the need of the education except to fulfil the acquirement of the skills. Education and literacy has never been able to define its meaning. And despite of being growing and exploring so many things in our day to day life we have not been able to achieve the sustainability in happiness. After so many years of carrying conventional education system, we are now talking about redefining it. Few very interesting questions arouse while writing this paper and they were like Why this topic?, Why do we need sustainability. And last but not the least that What made me writing this? Education or literacy? These are the few questions which arouse in my mind while thinking of this topic. There are many things which we aren’t in a mindset to talk about because we don’t know its relevance which our elders have told and now new generation is following it blindly. Where the brains are applied? We all need to ponder upon, we all need to think critically rather than following things with blindfolds. These were the ideas and thoughts which everyone come across but due to lack of information on how to achieve the sustainability it’s been a undercover agenda for we all to explore.